Two Independent Mutations in ADAMTS17 Are Associated with Primary Open Angle Glaucoma in the Basset Hound and Basset Fauve de Bretagne Breeds of Dog - Oliver, James A. C.; Forman, Oliver P.; Pettitt, Louise; Mellersh, Cathryn S. (PLOS ONE, 2015)
Purpose Mutations in ADAMTS10 (CFA20) have previously been associated with primary open angle glaucoma (POAG) in the Beagle and Norwegian Elkhound. The closely related gene, ADAMTS17, has also been associated with several different ocular phenotypes in multiple breeds of dog, including primary lens luxation and POAG. We investigated ADAMTS17 as a candidate gene for POAG in the Basset Hound and Basset Fauve de Bretagne dog breeds. Methods We performed ADAMTS17 exon resequencing in three Basset Hounds and three Basset Fauve de Bretagne dogs with POAG. Identified variants were genotyped in additional sample cohorts of both breeds and dogs of other breeds to confirm their association with disease. Results All affected Basset Hounds were homozygous for a 19 bp deletion in exon 2 that alters the reading frame and is predicted to lead to a truncated protein. Fifty clinically unaffected Basset Hounds were genotyped for this mutation and all were either heterozygous or homozygous for the wild type allele. Genotyping of 223 Basset Hounds recruited for a different study revealed a mutation frequency of 0.081 and predicted frequency of affected dogs in the population to be 0.007. Based on the entire genotyping dataset the association statistic for the POAG-associated deletion was p = 1.26 x 10−10. All affected Basset Fauve de Bretagne dogs were homozygous for a missense mutation in exon 11 causing a glycine to serine amino acid substitution (G519S) in the disintegrin-like domain of ADAMTS17 which is predicted to alter protein function. Unaffected Basset Fauve de Bretagne dogs were either heterozygous for the mutation (5/24) or homozygous for the wild type allele (19/24). Based on the entire genotyping dataset the association statistic for the POAG-associated deletion was p = 2.80 x 10−7. Genotyping of 85 dogs of unrelated breeds and 90 dogs of related breeds for this variant was negative. Conclusion This report documents strong associations between two independent ADAMTS17 mutations and POAG in two different dog breeds.